Bezpieczeństwo prawne danych osobowych w nowych warunkach cyfrowych - Chałubińska-Jentkiewicz, Katarzyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The protection of personal data in the new digital conditions requires redefinition and changes of the law. The development of new technologies means that the current legal provisions are not matched to new challenges in the protection of personal data. Therefore, this law is still changed and improved. The most important role is played by bodies appointed to comply with provisions relating to the protection of privacy. Important from the point of view of individuals - because it is their data protection – it also seem the awareness related to the existing threats resulting from the use of websites, in particular from social websites. Users using them are not always fully aware that the data placed on the network will not be used by unauthorized persons. This problem touches on issues such as: responsibility for content on the web, responsibility for services provided electronically, the right to be forgotten, jurisdiction in the area of global service provision. The legal protection, which is guaranteed by the new EU regulations, is only the starting point of the necessary changes in this area.